Efficacy of Intravitreal Anti Vascular Endothelial Growth Factor Injection Compared to Focal Therapy in Pediatric Patients with Coats Disease - Alia Nesa Utami; Julie Dewi Barliana (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2022)
Introduction: Coats disease is a retinal vascular disorder that may lead to progressive exudative retinal detachment. The standard regiment of treatment is focal therapy. However, its effectiveness may decrease when more than two quadrants of the retina exhibit vascular abnormalities. Thus, recent studies tried to use anti vascular endothelial growth factor (anti-VEGF) as therapy for the vascular problems. Aims: Comparing the efficacy between anti-VEGF injection and standard therapy regiment such as focal laser therapy. Methods: Literature searching was conducted through PubMed, ScienceDirect, Google Scholar, ProQuest, and SpringerLink. Search terms included